Diabetes and Phytomedicine - Saba Khan,; Nizam Uddin Farooqui, (International Journal of Phytomedicine, 2014)
Herbalism is the use of plants for medicinal purposes. The use of plants as medicines dates as far back as the origin of humankind. Plants have been the basis for medical treatments through much of human history, and such traditional medicine is still widely practiced today. Natural products from plant, animal and minerals have been the basis of the treatment of human disease. Today about 80 % of people in developing countries still rely on traditional medicine, based largely on species of plants and animals, for their primary health care. In recent years, there has been growing interest in alternative therapies and the therapeutic use of natural products, especially those derived from plants